Charge Transfer Interactions of p-Azoxyanisole Complexes for Electrooptical Activity - Shankar Kumar, Ch. Ravi; Deepthi, S.; Jha, Anjali (Asian Journal of Chemistry, 2020)
In particular interactions due to organic-inorganic molecules results self assembled structures organize supramolecular structures for molecular, electronic and electrooptical properties. Supramolecular structures originated are complexes with organic (p-azoxyanisole) molecule, synthesized with metal nanoparticles (iron, copper and aluminium.) Spectroscopic studies interpret infrared spectra with wavenumbers of characteristic bands in assigned regions; wavenumbers with reduced intensity in Raman spectra attribute metal-organic framework with charge transfer. Designed frame work with dense participation of carriers interpret electron correlation and exchange interaction specifying molecular, electronic and electrooptical properties with Gaussian package using electron density method. Deterministic procedure attribute vital role of charge transfer interactions responsible in formation of complex with improvement in properties responsible for electrooptical activity.